Validity of conventional anthropometric techniques for predicting body composition in healthy Chinese adults. Issue 1 (March 1995) - Eston, R G; Fu, F; Fung, L
Abstract : There is little information on the application of generalized prediction equations to ethnic groups other than Europeans and groups of European descent. The purpose of this study was to crossvalidate conventional equations on a group of 56 Chinese adults. Body density was assessed by underwater weighing and also predicted by equations which use a combination of selected skinfolds-biceps, triceps, pectoral, subscapular, abdominal, suprailiac, thigh and calf. There were significant correlations (P < 0.01) between the various methods of predicting percentage fat. However, analysis of variance revealed significant differences (P < 0.01) between mean values. In the men, the Jackson and Pollock equation underestimated, and the Durnin and Womersley equation overestimated, the percentage fat predicted by underwater weighing. The best predictor site in this group was the medial calf skinfold (r = 0.81), which is not included in either equation. In the women, the best predictor sites were the triceps, suprailiac and thigh. As these sites are also used in the Jackson et al. equation, it is not surprising that there was no difference between the prediction of percentage fat by this equation and underwent weight. It is concluded that the Durnin and Womersley and Jackson and Pollock equations tend to overestimate and underestimate, respectively, the percentage fat in Chinese men. Alternative equations which use the calf skinfold may be more appropriate for this ethnic group. In Chinese women, there appears to be good agreement between Jackson and Pollock and hydrodensitometric estimations of percentage fat.